Intracranial hypertension management - Nordon, David Gonçalves; Esposito, Sandro Blasi (Revista da Faculdade de Ciências Médicas de Sorocaba, 2009)
ABSTRACT Intracranial hypertension is a hazardous and common situation in the emergency room. Every effort must be made in order to avoid or reduce its secondary lesions. Advanced Trauma Life Support in the first evaluation is important, along with head computerized tomography, which is useful to identify surgical cases or anatomical lesions, and intracranial pressure monitoring. Mannitol is the mostly used drug to reduce intracranial pressure, but it must be used attentively, otherwise it may cause hypovolemic shock. Barbiturate coma and decompressive craniectomy are reserved to the refractory cases, as second tier procedures.